Creche em Presidente Prudente, SP - Bertocco, Jorgina Célia Corrêa [UNESP] (2012)
This work presents studies for the preparation of a project of kindergarten in the city of Presidente Prudente in state of São Paulo. Presents theoretical and conceptual research that allow us to analyze the history of childhood education in the country and its evolution over time, as well as studies of other kindergarten projects adopted as projective references and analysis of the intervention area